Global assessment of chemical quality of drinking water: The case of trihalomethanes - Villanueva CM; Evlampidou I; Ibrahim F; Donat-Vargas C; Valentin A; Tugulea A-M; Echigo S; Jovanovic D; Lebedev AT; Lemus-Pérez M; Rodriguez-Susa M; Luzati A; et al. (Elsevier Ltd)
BACKGROUND: Trihalomethanes (THM), a major class of disinfection by-products, are widespread and are associated with adverse health effects. We conducted a global evaluation of current THM regulations and concentrations in drinking water. METHODS: We included 120 countries (∼7000 million inhabitants in 2016), representing 94% of the world population. We searched for country regulations and THM routine monitoring data using a questionnaire addressed to referent contacts. Scientific and gray literature was reviewed where contacts were not identified or declined participation. We obtained or estimated annual average THM concentrations, weighted to the population served when possible. RESULTS: Drinking water regulations were ascertained for 116/120 (97%) countries, with 89/116 (77%) including THM regulations. Routine monitoring was implemented in 47/89 (53%) of countries with THM regulations. THM data with a varying population coverage was obtained for 69/120 (58%) countries consisting of ∼5600 million inhabitants (76% of world's population in 2016). Population coverage was ≥90% in 14 countries, mostly in the Global North, 50-89% in 19 countries, 11-49% among 21 countries, and ≤10% in 14 countries including India, China, Russian Federation and Nigeria (40% of world's population). DISCUSSION: An enormous gap exists in THM regulatory status, routine monitoring practice, reporting and data availability among countries, especially between high- vs. low- and middle-income countries (LMICs). More efforts are warranted to regulate and systematically assess chemical quality of drinking water, centralize, harmonize, and openly report data, particularly in LMICs.
(c) The Author/s
Keywords: Chemicals; Disinfection by products; Drinking water; International; Quality; Regulation; Routine monitoring; Trihalomethanes; Drinking Water; Trihalomethanes; Water Supply; Water Pollutants, Chemical; Disinfection